2015
DOI: 10.1038/ejhg.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence: shared genetic basis between Mendelian disorders and a polygenic trait

Abstract: Multiple inquiries into the genetic etiology of human traits indicated an overlap between genes underlying monogenic disorders (eg, skeletal growth defects) and those affecting continuous variability of related quantitative traits (eg, height). Extending the idea of a shared genetic basis between a Mendelian disorder and a classic polygenic trait, we performed an association study to examine the effect of 43 genes implicated in autosomal recessive cognitive disorders on intelligence in an unselected Dutch popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…We also identified a LoF mutation in TMEM135, previously been reported in the large Iranian NS-ARID cohort by Najmabadi et al, 2011 (in which a missense mutation, Cys228Ser was reported) 11 , and in Wright et al, 2014 (missense) 46 , also as a quantitative trait locus for intelligence 47 .…”
Section: Homozygous Loss-of-function Mutationssupporting
confidence: 76%
“…We also identified a LoF mutation in TMEM135, previously been reported in the large Iranian NS-ARID cohort by Najmabadi et al, 2011 (in which a missense mutation, Cys228Ser was reported) 11 , and in Wright et al, 2014 (missense) 46 , also as a quantitative trait locus for intelligence 47 .…”
Section: Homozygous Loss-of-function Mutationssupporting
confidence: 76%
“…Thus, although linkage and association studies have identified strong evidence of a genetic influence, many rarer variants with aetiological relevance may be overlooked because they will not be captured by single nucleotide polymorphism (SNP) arrays, or do not reach stringent significance parameters. Recent findings indicate that the boundary between common traits and monogenic forms of disorder may be less defined than previously thought2526. Accordingly, with advances in molecular technologies, examples can be drawn from the literature of rare or private high-penetrance variants that contribute to certain forms of speech and language deficits24.…”
mentioning
confidence: 99%
“…Experience with other complex human traits seemed to hold promise that variants in genes known through Mendelian (monogenic) disorders would also predict normal variation. Yet, genetic variation in known ID genes did not live up to this promise at present sample sizes [3,4]. Studies on parental age, a well-validated proxy variable for new mutations not shared with the parents [5], showed associations with ID and autism.…”
mentioning
confidence: 99%
“…Alternatively, if genetic interactions play the role that we ascribe to them here, we also need to consider stabilizing selection, where selective pressures have worked to make intelligence robust to genetic and environmental perturbations in either direction [21], not to increase it as much as possible. Because of that possibility, researchers should not build the assumption that very high IQ is continuous with normal intelligence into their studies by default [3,4,21]. Once enough data is in, complex models and simulations will allot roles to these mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation